2018
DOI: 10.3390/nu10010047
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Secondary Prevention of Nutritional Deficiencies in High-Risk Groups in High-Income Countries

Abstract: Surveys in high-income countries show that inadequacies and deficiencies can be common for some nutrients, particularly in vulnerable subgroups of the population. Inadequate intakes, high requirements for rapid growth and development, or age- or disease-related impairments in nutrient intake, digestion, absorption, or increased nutrient losses can lead to micronutrient deficiencies. The consequent subclinical conditions are difficult to recognize if not screened for and often go unnoticed. Nutrient deficiencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 69 publications
(75 reference statements)
0
29
0
Order By: Relevance
“…Furthermore, the WHO and the Food and Agriculture Organization (FAO) of the United Nations have described that, based on blood markers, vitamin A and iron deficiencies are widespread and of significant global concern [46, 49,50]. Status data in the general population or specific subpopulations also reveal inadequacies or deficiencies in various countries, including in developed nations, for vitamins B6, B12, and folate, as well as zinc and selenium [53,59,60,[68][69][70][71][72][73]. Finally, a global survey of EPA + DHA status in the blood, from 298 studies, found "low" or "very low" status (i.e., levels associated with increased risk of cardiovascular related mortality) of EPA + DHA in most of the countries assessed [74].…”
Section: Nutritional Impact On Immunitymentioning
confidence: 99%
“…Furthermore, the WHO and the Food and Agriculture Organization (FAO) of the United Nations have described that, based on blood markers, vitamin A and iron deficiencies are widespread and of significant global concern [46, 49,50]. Status data in the general population or specific subpopulations also reveal inadequacies or deficiencies in various countries, including in developed nations, for vitamins B6, B12, and folate, as well as zinc and selenium [53,59,60,[68][69][70][71][72][73]. Finally, a global survey of EPA + DHA status in the blood, from 298 studies, found "low" or "very low" status (i.e., levels associated with increased risk of cardiovascular related mortality) of EPA + DHA in most of the countries assessed [74].…”
Section: Nutritional Impact On Immunitymentioning
confidence: 99%
“…Inadequate or even deficient nutrient intake and status is still widely prevalent at global level and, although generally underacknowledged, is a main risk factor for NCDs [20]. Nutrient surveys indicate that the aging population is at particular risk for poor nutrient intake and status, which may result in increased risk for chronic fatigue, and cardiovascular, cognitive, and neuromuscular disorders in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Health policies and interventions to improve dietary intake at the population level are essential to reverse the global trend towards unhealthy dietary patterns and physical inactivity. However, more individualized approaches may be needed to address persistent nutritional gaps and prevent future morbidity in high-risk groups such as the older population [19,20]. An estimated 5% to 10% of community-dwelling adults >70 years of age are undernourished; this proportion rises to 30% to 65% among institutionalized elderly patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensuring young children meet recommended nutrient intakes is important because early childhood is a critical time period for growth and development [1]. Although the United States (US) is a developed country, some children are not meeting the recommended micronutrient intakes for ideal growth and development [2,3]. Inadequacies in intakes for vitamin D, vitamin E, and potassium, as well as excessive intakes of vitamin A, zinc, and sodium, have been reported among US infants, toddlers, and preschoolers [3].…”
Section: Introductionmentioning
confidence: 99%